مدى اعتماد الصيدليات على المعايير القياسية في تقديم الخدمات الصيدلانية في المستشفيات العامة بمدينة بنغازي - الغصني سوفيناج خالد; العمامي هبة حسن; العشيبي آية حمد; الصالحين آية على; الشيباني فدوى منصور (Scientific Journal of University of Benghazi, 2022)
The purpose of the study is to examine the extent of compliance with accreditation criteria in the pharmacy departments at Benghazi hospitals are matched. Objectives: To assess the extent that the pharmacy conforms to organizational structure standards as well as to measure the extent to which prescribing standards are available and the extent to which pharmacists understands the standards of their duties as pharmacists and to assess the adequacy of drug storage standards. Research methodology: This descriptive study reviews the extent to which the accreditation criteria for the management of pharmacy in Benghazi city hospitals are being met. Study population: Hospital pharmacies in Benghazi; the Galaa Hospital, the Jumhuriya Hospital, the Psychiatric Hospital, the Sadriya Hospital, the Hawari Hospital, Benghazi Medical Center and the Children's Hospital. Research methodology: A cross-sectional descriptive study to assess compliance with quality standards at the pharmacies of hospitals in Benghazi. Results: The pharmacies in question differed in the level of accreditation for all standards of services provided, as the accreditation was complete (above 80% of benchmark points) in conforming to standards for the Sadriya hospital pharmacy (98.8%) and Hawari (80.6%) while the remaining pharmacies at the Children's Hospital (58.7%) and Benghazi Medical Centre (67%) and the Psychiatric hospital (54.3%), for which the level of dependency was estimated to be partial (50% -80% of benchmark points). Al-Galaa Hospital (45.8%) and Al-Jumhuriya Hospital (41.6%) were the lowest in accreditation. Recommendations: This study recommends establishing standard accreditation measures for hospital pharmacies in Benghazi, where the pharmacy must have a clear organizational structure. Additionally, a hospital pharmacy must operate 24 hours for emergency patients, hypnotics and outpatient prescriptions to provide better services to patients.